Development of E-Comic Media Assisted by Class Minimum Competency Assessment (AKM) for Enhancing Competency in Elaborating Fairy Tale Messages among Lower Grade Students - Mulyani; Purwati, Panca Dewi; Sabilillah, Nugraheti Sismulyasih (Universitas Muhammadiyah Malang, 2024)
Reading comprehension is the process of understanding information in a passage. Students with limited proficiency to elaborate fairy tale messages are the basis for this research. Students have the capability to read, but they have not reached the level of understanding the content the readings. The utilization of educational resources is restricted solely to books at present. This research aims to determine the design development, feasibility, and effectiveness of controlled e-comic media assisted by class minimum competency assessments (AKM) in improving student learning outcomes regarding the competency to elaborate fairy tale messages for third-grade elementary school students. The method used in this study is Research and Development using the Borg and Gall development model. Product validity testing is carried out by material expert validators and media expert validators. The results of this research show that the media feasibility test results obtained were 88% with the title very feasible and the feasibility test results from material experts were 90% with the title very feasible. The results of the large-scale trial showed improvement from pre-test to post-test with an average N-Gain of 0.67 and significance (2-tailed) of 0.000 < 0.05. The conclusion of this research indicates that controlled e-comic media assisted by minimum competency assessment (AKM) class is deemed feasible and effective in improving the competency of elaborating the message of fairy tales for third-grade students at SDN 1 Sangge and SDN 2 Sangge.